Impact of structured checklist-based preoperative counseling versus standard counseling on postoperative patient-reported outcomes after elective surgery - Moh'd S. Dawod; Mohammad N. Alswerki; Ahmad Alelaumi; Moath G. Shaqar; Farah M. Al-Habashneh; Saif A. Alshloul; Mustafa Burghol; Samer F. Al-Rawashdah; Mohammad W. Amir; Mahmoud H. Alkhasawneh (BMC, 2024)
Abstract Introduction Surgery, even on an elective-basis, often induces significant stress in patients, characterized by preoperative anxiety and heightened stress levels due to anticipation of the unknown. However, the primary objective of preoperative counseling is to mitigate these concerns, particularly when delivered in a structured and comprehensive manner. While previous research has highlighted the beneficial impact of preoperative counseling on patient-reported outcomes, none have specifically explored the implementation of a structured checklist-based approach during counseling sessions. To bridge this gap in the literature, our study aims to investigate the effects of implementing a checklist-based structured counseling approach on patient-reported outcomes following elective surgery. Methods In this prospective cohort study conducted over one year from January to December 2023, a total of 600 patients undergoing elective surgery across three specialties-orthopedic surgery, general surgery, and urology-were examined. The patients were divided into two groups: an intervention group consisting of 300 patients and a control group with an equal number of patients. The study evaluated three key outcomes-postoperative pain, anxiety, and satisfaction-at three specific time points following surgery: 24 h, 48 h, and 72 h. Results Patients receiving structured checklist counseling showed significantly lower pain scores (24 h: 6.6 vs. 7.03, p = 0.041; 48 h: 5.62 vs. 6.55, p = 0.029; 72 h: 2.54 vs. 2.90, p = 0.035) and anxiety scores (24 h: 8.58 vs. 9.25, p = 0.039; 48 h: 7.50 vs. 8.45, p = 0.030; 72 h: 4.53 vs. 5.98, p = 0.031), as well as higher satisfaction scores (24 h: 5.99 vs. 5.06, p = 0.043; 48 h: 6.99 vs. 6.02, p = 0.033; 72 h: 9.10 vs. 8.20, p = 0.039) compared to controls. These improvements were consistently significant across all three surgical specialties studied (p < 0.05). Conclusion The structured checklist-based counseling method proves to be effective and essential. This method is associated with reduced postoperative pain and anxiety levels, along with increased patient satisfaction, when compared to the standard approach. Level of evidence Prospective non-randomized study, Level II.